2023
DOI: 10.1002/anie.202313522
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Local CO2 Adsorption by L‐histidine Incorporation for Selective Formate Production Over the Wide Potential Window

Yicheng Li,
Ernest Pahuyo Delmo,
Guoyu Hou
et al.

Abstract: Electrochemical carbon dioxide reduction reaction (CO2RR) to produce valuable chemicals is a promising pathway to alleviate the energy crisis and global warming issues. However, simultaneously achieving high Faradaic efficiency (FE) and current densities of CO2RR in a wide potential range remains as a huge challenge for practical implements. Herein, we demonstrate that incorporating bismuth‐based (BH) catalysts with L‐histidine, a common amino acid molecule of proteins, is an effective strategy to overcome the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 51 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…4(a), the CO 2 electroreduction into formate comprises two primary steps: (1) the conversion of CO 2 molecules into *OCHO intermediate via a process involving the transfer of a proton–electron pair and (2) the subsequent conversion of *OCHO into *HCOOH intermediate through a proton-coupling electron transfer process, resulting in the generation of formate as the final product. 67 Furthermore, the formation of key reactive intermediates such as *OCHO and *HCOOH has been verified using in situ spectral characterization techniques during CO 2 RR 68,69 (Fig. 4(b)–(d)).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…4(a), the CO 2 electroreduction into formate comprises two primary steps: (1) the conversion of CO 2 molecules into *OCHO intermediate via a process involving the transfer of a proton–electron pair and (2) the subsequent conversion of *OCHO into *HCOOH intermediate through a proton-coupling electron transfer process, resulting in the generation of formate as the final product. 67 Furthermore, the formation of key reactive intermediates such as *OCHO and *HCOOH has been verified using in situ spectral characterization techniques during CO 2 RR 68,69 (Fig. 4(b)–(d)).…”
Section: Discussionmentioning
confidence: 83%
“…127 The Gemini surfactants, with their double quaternary ammonium cations and alkyl chains, serve the dual purpose of stabilizing the crucial intermediate HCOO* and facilitating the accessibility of CO 2 . Additionally, l -histidine, 68 polyethylene glycol, 124 vitamin C, 128 sulfur anions, and sodium cations 129 have also been reported for surface modification of Bi-based catalysts. However, currently, there is no research reported on whether these surface modifiers for Bi-based materials can effectively retain their presence on the catalyst surface during the long-time electrocatalytic CO 2 RR test process.…”
Section: Discussionmentioning
confidence: 99%
“…Even at a low level of 15 %, the FE of urea reaches as high as 42.33 % that is already close to the optimal FE when using a flow cell. This result is intriguing, since the CO 2 level significantly affects the reaction rate of CO 2 RR [24] and thereby the surface coverage of CO 2 RR intermediates, if participant in CÀ N coupling is the CO 2 RR intermediates, it is apparently that the efficiency and selectivity of CÀ N coupling can be notably influence by CO 2 level. [25] Consequently, the limited influence of CO 2 concentration on urea FE would suggest the participant in CÀ N coupling being CO 2 itself.…”
Section: Methodsmentioning
confidence: 99%
“…An electrochemical CO 2 reduction reaction (CO 2 RR) has been recently demonstrated to be an effective strategy to use excess sustainable electricity for upgrading CO 2 into value-added chemicals (such as HCOOH or C 2 H 4 ). [4][5][6][7][8][9][10] Notably, compared with metal-ion or metal-air batteries, [11][12][13][14][15][16] metal-CO 2 batteries do not only reduce CO 2 into products of high value but also provide energy during the discharging process, which is regarded as an extra advantage compared to the individual electrochemical CO 2 conversion. 17,18 Therefore, metal-CO 2 batteries on a larger scale can become a powerful tool for both energy and raw material management.…”
Section: Introductionmentioning
confidence: 99%